2004
DOI: 10.1002/app.20112
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of unsaturated polyester–montmorillonite intercalated hybrid

Abstract: An unsaturated polyester-organophilic montmorillonite hybrid was prepared by dispersing polymerizable quaternary ammonium-modified montmorillonite in an unsaturated polyester resin, followed by crosslinking reaction. The purpose of this investigation was to discover the role of the polymerizable group of quaternary ammonium in improving interfacial interaction between the silicate layers and polymer chains and the mechanical properties of unsaturated polyester-montmorillonite hybrids. It is found that when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…on flammability properties of UP resin incorporating nanoclays, Lee and coworker15 on shrinkage control of UP nanocomposites, Inceoglu and Yilmazer16 on mechanical properties of UP‐based nanocomposites. There are also some reports available on impact response of nanocomposite reinforced thermoset materials,16–20 Beheshty et al 17. studied UP resin reinforced organically modified clay (OMC) nanocomposites, and reported 51.7% improvement in Izod impact strength at 1% OMC loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…on flammability properties of UP resin incorporating nanoclays, Lee and coworker15 on shrinkage control of UP nanocomposites, Inceoglu and Yilmazer16 on mechanical properties of UP‐based nanocomposites. There are also some reports available on impact response of nanocomposite reinforced thermoset materials,16–20 Beheshty et al 17. studied UP resin reinforced organically modified clay (OMC) nanocomposites, and reported 51.7% improvement in Izod impact strength at 1% OMC loading.…”
Section: Introductionmentioning
confidence: 99%
“…showed the impact strength of the epoxy nanocomposites containing nanoclay (Cloisite 30B) is significantly improved by the filler addition. Zhang et al 19. studied UP–organophilic montmorillonite (MMT) hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was attributed to the high polarity of hydroxypropyl acrylate which may disturb the preintercalation of UPR into the galleries of montmorillonite. The UPRs with a styrene monomer were used in dispersions with polymerizable quaternary ammonium-modified montmorillonite [225]. An increase in tensile and impact strength and heat resistance (Table 29) was found when 2-5 wt % organophilic montmorillonite was added.…”
Section: Upr-based Nanocompositesmentioning
confidence: 99%
“…Furthermore, some researchers suggested that the exfoliation degree of the polymerizable clay could be influenced by the position of the reactive functional group, 16,24,37 and a crosslinking structure was found during the preparation. 25,28,32,33,37 However, the reason why the polymerizable clay is more exfoliatable than the nonpolymerizable clay is still unclear. Obviously, such knowledge could be very useful in designing exfoliated nanocomposites with enhanced interfacial interaction.…”
Section: Introductionmentioning
confidence: 98%